Analiza obratovalnega hrupa in vibracij okrova radialne črpalke - Predin, Andrej (Strojniški vestnik, 2000)
This paper surveys theoretical and experimantal studies of fluid mechanic vibration and noise. The experimental measurements were carried out in a radial one-stage pump which operates with clean cold water. Several experimental measurements were carried out on a radial one-stage pump which operates with clean cold water. Several experimental measurements on the operating characteristics such as capacity-head, capacity-efficiency, capacity-operating noise and capacity-pump casing vibration amplitudes under different operating regimes (different impeller speed) were performed. Measurement results are given in time and frequency domains.
Keywords: črpalke radialne; hrup črpalk; meritve vibracij; minimiranje hrupa; radialne črpalke; hrup; vibracije; obratovalne karakteristike